Effects of calcium supplementation on oxidative status and oxidative damage in great tit nestlings inhabiting a metal-polluted area - Sanchéz-Virosta Pablo; Espín Silvia; Ruiz Sandra; Stauffer Janina; Kanerva Mirella; García-Férnandez Antonio J.; Eeva Tapio (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
Calcium has been proposed to diminish metal toxicity by the modulation of the oxidative stress. This study explores the effects of Ca availability and metal exposure on oxidative stress biomarkers in great tit (Parus major) nestlings. Nests were supplemented with Ca (Ca-supplemented group) or not supplemented (Control group) in a metal-polluted and a background zone in SW Finland. Metal concentrations were analyzed from feces. We analyzed antioxidants (tGSH, GSH:GSSG ratio, CAT, GST, GPx, SOD), protein carbonylation and lipid peroxidation in red cells of nestlings.Ca-supplemented and fast-growing nestlings showed higher CAT activity to cope with reactive oxygen species (ROS) generated during intensive growth and metabolism. SOD and GPx (the latter not statistically significant) were more active in the polluted area, possibly reflecting higher ROS production in nestlings from this zone due to the enhanced metal exposure and smaller size. Antioxidant levels changed over the range of metal concentrations depending on the Ca levels in plasma, suggesting that higher Ca levels stimulate antioxidants and mitigate the impacts of metals. Ca supplementation may improve nestling traits and reproductive output when antioxidants are enhanced in a situation of oxidative challenge. Therefore, Ca should be considered in future studies assessing metal exposure and effects on wild birds.